Teaching human senses to standard one students' using cognitive theory / Naizatul Akmal Karizaman - Karizaman, NaizatuI Akmal (2006)
The advent of new technologies brings major changes in our way of life. These advances might not be achievable without knowledge and the key to knowledge is education. Nowadays, researchers are finding new ways in educating people as we are faced with new challenges everyday. Education has been improving a lot compared to years ago. Computers have taken the place as the learning and teaching tool and have been considered as a need rather than a luxury. In parallel with this phenomenon, the usage of multimedia has become common. It has also created a new interest of developing learning strategies to accommodate education integrated in multimedia. In relevant to that, this project concerns with the development of a courseware to teach human senses using cognitive theory. The theory consists of six steps which emphasizes on the learners actively construct their own understanding rather than be a passive recipient of infomnation. The role of a teacher or instructor is to provide guide and support such as corrective feedback which will enable the learner to create accurate mental connections which later builds up knowledge in learner's mind. In developing the project. Multimedia Project Development Cycle which consists of eight phases has been used as the methodology.The target audiences for the project is standard one students who's taking the science subject. The purpose is to create an effective multimedia courseware for teaching human senses. The project has been tested to a group of standard one students along with a few teachers and has received good feedback. It was found that the cognitive theory is suitable in teaching human senses.